Spraying of Composite Liquid Fuels Based on Types of Coal Preparation Waste: Current Problems and Achievements: Review - Roman Volkov (MDPI AG, 2021)
This article discusses the atomization of composite liquid fuels. A large group of injectors is considered. A comparative analysis of the atomization characteristics (droplet sizes and velocities, jet opening angles) and the influence of the fuel characteristics (density, viscosity, component composition) and the process parameters (the ratio of the fuel–air mass flow rates, the features of the jet formation) has been carried out. Finally, the most effective types of injectors, which provide for the necessary characteristics of fuel atomization for its combustion, have been determined. The most favorable conditions for the applicability of each type of atomization have been formulated. Possible mechanisms of secondary fragmentation of droplets of composite fuels have been analyzed: those resulting from mutual collisions of droplets in the flux and from the interaction with a solid surface as well as those resulting from thermal overheating in the presence of a phase boundary or a large gradient of component volatility. A conclusion is made about the need of using a synergistic effect of primary and secondary atomization of fuel suspension droplets.